Development and application of an approach for safety assessment of radioactive waste storage facilities for accidental scenarios - Stela Dalva Santos Cota; Ricardo Gomes Passos; Vanderley de Vasconcelos (Brazilian Journal of Radiation Sciences, 2021)
Worldwide there is a huge amount of radioactive waste, including disused sources, decommissioning waste, and naturally occurring radioactive material (NORM) waiting for final disposal, the so-called storage facilities. Results of safety assessment of such facilities are usually required in decision-making during design, modification, safety improvements, periodic safety reviews, and licensing activities. Quantitative safety assessment methodologies used in many areas of nuclear industry involves the evaluation of risk through the definition of scenarios, likelihoods, and consequences, for normal operation and accidents. There are many techniques that can be used in each one of these steps. For screening the accident scenarios, qualitative techniques such as failure modes and effect analysis (FMEA) are available. For a quantitative assessment of occurrence probabilities of undesired events, logical and graphical tools such as fault tree analysis (FTA) are employed. Consequence assessments involve the dose assessment in the workers and the impact of the released materials in the environment and of public exposure to radiation. This work analyzes the application of these traditional safety assessment approaches to storage facilities and how they can be applied to complement specific methodologies used in this area, such as the Safety Assessment Driving Radioactive Waste Management Solutions (SADRWMS), implemented in Safety Assessment Framework (SAFRAN) software tool, made available by International Atomic Energy Agency (IAEA).